Intermediate result of negative consequences of the epidemic of the new coronavirus infection for the global economy - T. V. Bakhturazova; M. K. Mayorov; P. S. Seleznev; D. A. Edelev (Вестник университета)
The epidemic of the new SARS-CoV-2 coronavirus infection slowed global economic growth and became the main threat for the global economy and financial markets in 2020. Authorities in many countries around the world have declared a health emergency. Without the experience of state quarantine, countries have faced negative consequences for citizens, the economy and financial market participants. The introduction of temporary regulatory easing in the context of the spread of a new coronavirus infection assisted to partially limit the negative consequences. The next few months will, probably, have a particularly strong impact on small business, as government support schemes are reduced or ceased. The article reveals the main consequences of the new coronavirus infection for the global economy.